INNOVATION TECHNOLOGY CLUSTERS USE OF TECHNOLOGY IN ILLUSTRATION - Eralievich, Sultanov Khaytoy (International Journal of Psychosocial Rehabilitation, 2020)
The article provides the theoretical foundations for innovative approaches to building partnerships between schools and universities, the need for creating an innovative cluster of pedagogical education as a new mechanism for mutual control, positive competition and private interests, the main stages of its formation, schools and universities. mechanisms of interaction between educational institutions. The form and content of the activities of the participants of the educational cluster, as well as the establishment of innovative “School- Laboratory” platforms for ensuring connection between the educational process and practice will be considered.